2007
DOI: 10.1007/s00424-007-0388-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of AFM in understanding biomineral formation in diatoms

Abstract: We review previous work and present new data on the application of atomic force microscopy (AFM) to study biomineral formation in diatoms, unicellular algae that make cell walls of silica. Previous studies examined a small subset of mostly larger diatom species, identifying a prevalence of large particulate silica on the nanoscale. We survey different structures including valves, girdle bands, and elongated spines called setae, in a variety of species, and show a diversity of nano-and meso-scale silica morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…S5). Similar observations were made in AFM studies of select diatom cell surfaces (41). In comparison, silica templated by single component protein hydrogel scaffolds was observed to be granular with a primary feature size of approximately 16 nm (35).…”
Section: Resultssupporting
confidence: 76%
“…S5). Similar observations were made in AFM studies of select diatom cell surfaces (41). In comparison, silica templated by single component protein hydrogel scaffolds was observed to be granular with a primary feature size of approximately 16 nm (35).…”
Section: Resultssupporting
confidence: 76%
“…From the two taxa the diatoms and the siliceous sponges, the importance of the organic templates for the formation of their biomineralic skeletons has been well elucidated. The ornate and elaborated diatom frustules are formed onto organic templates (Kröger et al, 1994;Kröger et al, 1997;Kröger et al, 1999;Sumper and Brunner, 2008;Hildebrand et al, 2008), the biosilica-associated peptides (silaffins) and the long-chain polyamines (see Poulsen et al, 2003). Furthermore, it was found that those organic molecules accelerate silica formation from a silicic acid solution in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…[5,17,20c,21,22] Several nanostructural features, such as ridges around frustule pores, zig-zag channels, and hillock topography of the outer plate (cribellum), were also elucidated by AFM, but their function remains unknown. [17,21] …”
Section: Formation Of Biological Nanostructuresmentioning
confidence: 99%